2022
DOI: 10.1109/tmtt.2022.3140751
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Mounted Parallel-Plate Coupler for Cylindric Dielectric Waveguides

Abstract: Surface-mounted parallel-plate capacitors (PPCs) can be used as transducing elements in wireless communication, for example in human body-dedicated applications, such as healthcare monitoring or activity tracking, which require robust wireless communications and user-convenient implementation. In this context, PPCs are an attractive element due to their mobility, noninvasive positioning, and small form factors. Moreover, they are relatively easy to analyze with a simple design. This work studies the use of PPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…5 shows that for 𝑑 > 3π‘π‘š, the cylindrical model is an excellent predictor of the propagation along the arm of the anatomical model. The results presented here are in line with previous results, where we showed that PPCs can be used to excite propagating modes along dielectric cylinders [5] and that they can be used for BCC communication around 450 MHz [3].…”
Section: B Post Processingsupporting
confidence: 93%
See 2 more Smart Citations
“…5 shows that for 𝑑 > 3π‘π‘š, the cylindrical model is an excellent predictor of the propagation along the arm of the anatomical model. The results presented here are in line with previous results, where we showed that PPCs can be used to excite propagating modes along dielectric cylinders [5] and that they can be used for BCC communication around 450 MHz [3].…”
Section: B Post Processingsupporting
confidence: 93%
“…The trend in propagation along a real human arm can be predicted accurately using a cylindrical model. Since propagation along a cylindrical, lossy waveguide can be described analytically [1,5], this opens up the possibility of a theoretical analysis of this frequency dependent propagation. Using modal analysis of the cylindrical model, we aim to show that also in this configuration this effect is due to surface waves which are tied to propagating modes along the arm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation